Pengendalian penyakit tidak menular berbasis posbindu - Dewi Ariyani Wulandari; Nur Hidayat; Susi Damayanti (STIKes Surya Global Yogyakarta, 2022)
The existence of Posbindu PTM in an effort to early detect non-communicable disease (NCD) risk factors in the Sleman Regency has increased significantly from 2018-2020. However, the implementation of the Posbindu PTM in Sleman Regency has not yet matched the target and has not been carried out routinely. The purpose of this study is to find out how the implementation of Posbindu PTM in Sleman Regency. The methodology of this research was qualitative with a case study approach. The data was taken by using interviews and observation by field noting. In this study, there were 41 main informants and 6 triangulated informants. Data analysis used content analysis in reducing data, presenting data, and drawing conclusions. The result of this research was that the implementation of Posbindu PTM has been based on the Regent's Regulation. Resources have obstacles including the absence of special funding for PTM Posbindu activities, the ability and adequacy of cadres, and the incompleteness of facilities and infrastructure. Another problem is the ability to coordinate between cadres has not been maximized so that it has not motivated the participation of the target groups of productive age and teenagers. The implementation of policies by the Health Office and Puskesmas officers has been good but has not been followed by the commitment of Posbindu cadres